PENERAPAN MODEL KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA MATERI PERUBAHAN WUJUD BENDA DI KELAS 4 SD INPRES LASIANA KOTA KUPANG - Nalle, Anselmus; Taty R. Koroh; Netty Elisabeth Antoneta Nawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The study, entitled "Implementation of the Student Teams Achievement Division Cooperative Model to Improve Science Learning Outcomes on the Changes in State of Matter Subject in Grade IV of SD Inpres Lasiana, Kupang City," aims to improve science learning outcomes through the application of the Student Teams Achievement Division cooperative model on the change in state of matter subject in Grade IV of SD Inpres Lasiana, Kupang City. The researcher chose classroom action research as the type of research used, which includes four procedures: planning, implementation, observation, and reflection, carried out in two cycles. The subjects in this study were all 30 students of Grade IV B of SD Inpres Lasiana. The data collection techniques used were observation and testing, using observation sheets and test questions as research instruments. The data analysis technique used by the researcher was quantitative descriptive analysis by finding the average value and percentage of learning completion. In the first cycle, the percentage of student learning completion was only 53.33% and increased significantly to 96.67% in the second cycle. Keywords: STAD Type Cooperative Model, Science and Science, and Learning Outcomes